2022
DOI: 10.1080/22221751.2022.2065933
|View full text |Cite
|
Sign up to set email alerts
|

Sexually-transmitted hepatitis C virus reinfections among people living with HIV in Taiwan: the emerging role of genotype 6

Abstract: Hepatitis C virus (HCV) reinfections after successful treatment with direct-acting antivirals (DAAs) pose a significant challenge to HCV elimination, especially among high-risk people living with HIV (PLWH). In this study, PLWH who had achieved HCV viral clearance with DAAs were included between January 2018 and June 2021. PLWH having acquired HCV infections after 2017 were classified as “recent-infection group,” and those before 2017 as “remote-infection group,” and the incidences of HCV reinfection were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Increasing trends of recently acquired HCV infections had been noted among PLWH who were predominantly MSM and HCV seronegative at baseline in Taiwan during 1994 to 2018, with an HCV seroincidence rate reaching 28.10 per 1,000 person-years of follow-up (PYFU) in 2018 ( 25 , 26 ). The rate of HCV reinfection was estimated to be 82 per 1,000 PYFU ( 27 , 28 ). Syphilis was consistently found to be statistically significantly associated with HCV infections in all these studies ( 25 28 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing trends of recently acquired HCV infections had been noted among PLWH who were predominantly MSM and HCV seronegative at baseline in Taiwan during 1994 to 2018, with an HCV seroincidence rate reaching 28.10 per 1,000 person-years of follow-up (PYFU) in 2018 ( 25 , 26 ). The rate of HCV reinfection was estimated to be 82 per 1,000 PYFU ( 27 , 28 ). Syphilis was consistently found to be statistically significantly associated with HCV infections in all these studies ( 25 28 ).…”
Section: Methodsmentioning
confidence: 99%
“…The rate of HCV reinfection was estimated to be 82 per 1,000 PYFU ( 27 , 28 ). Syphilis was consistently found to be statistically significantly associated with HCV infections in all these studies ( 25 28 ). In Taiwan, DAAs have been reimbursed by the National Health Insurance (NHI) since 2017 ( 29 , 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…The 38 studies included in the pooled HCV reinfection incidence estimate comprised 8931 participants at risk of reinfection (Table S1). Berenguer et al, 19 and Chen et al 20 included two study population arms (PWID and MSM) and HCV reinfection incidence rates were extracted for each arm and assigned to each key population meta‐analysis separately. The pooled incidence estimate from all included studies was 4.13 per 100 py (95% confidence interval [CI]: 3.45–4.81) with HCV reinfection incidence ranging from 0.00 per 100 py to 31.00 per 100 py across studies.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-seven studies reported reinfection among PWID, 9 among MSM and 3 among people in custodial settings (two studies reported on both PWID and MSM 19,20 ). No studies reporting reinfection among transgender people were identified.…”
Section: Included Studiesmentioning
confidence: 99%